Analisis Pengelolaan Destinasi Pantai Parangtritis Berdasarkan Komponen Pariwisata 6a - Arinta Destri Larasati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Effective destination management plays a crucial role in enhancing the competitiveness and sustainability of tourism destinations. Parangtritis Beach, one of the leading tourist destinations in the Special Region of Yogyakarta, possesses significant natural, cultural, and man-made tourism potential that requires comprehensive management. This study aims to analyze the management of Parangtritis Beach based on the 6A tourism components, namely Attraction, Accessibility, Amenities, Available Packages, Activities, and Ancillary Services. A descriptive qualitative approach was employed, with data collected through observations, interviews, and documentation. Informants were selected using purposive sampling and included destination managers, members of the Tourism Awareness Group (Pokdarwis), tourism business operators, and tourists. The findings indicate that the Attraction, Accessibility, Amenities, and Activities components have been managed effectively and serve as the main strengths of the destination. However, the Available Packages and Ancillary Services components require further improvement, particularly in developing integrated tourism packages and strengthening coordination among stakeholders. The results are expected to provide practical recommendations for destination managers and local governments to improve destination management, enhance tourist satisfaction, and support the sustainable competitiveness of Parangtritis Beach.